2003
DOI: 10.1046/j.1439-0434.2003.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield Loss Associated with Soya Bean Rust (Phakopsora pachyrhizi Syd.) in Uganda

Abstract: Studies were conducted to quantify the yield loss attributable to soya bean rust, a relatively new disease in Uganda. This was carried out for three consecutive seasons in the central, eastern, northern and western parts of the country, using three commercial varieties (Nam 1, Nam 2 and Namsoy 3) and two elite varieties (UG‐5 and GC‐00138‐29). The commercial varieties recorded higher yield losses (26.9–36.3%) and higher rust severities >50%, whereas the elite varieties recorded lesser yield losses of <10% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 4 publications
1
29
0
8
Order By: Relevance
“…In Uganda, Kawuki et al (2004) showed that rainfall, especially during mid-growth period of the crop, was important for examining soybean cultivar reactions. For example, the authors did not observe any differences among soybean cultivars and their reaction to ASR during a rainy season, when the highest ASR severities and infection rates were observed.…”
Section: Overall Effects Of Meteorological Factors On Field Epidemicsmentioning
confidence: 99%
“…In Uganda, Kawuki et al (2004) showed that rainfall, especially during mid-growth period of the crop, was important for examining soybean cultivar reactions. For example, the authors did not observe any differences among soybean cultivars and their reaction to ASR during a rainy season, when the highest ASR severities and infection rates were observed.…”
Section: Overall Effects Of Meteorological Factors On Field Epidemicsmentioning
confidence: 99%
“…bras., Brasília, v.43, n.10, p.1277-1286, out. 2008 podem ser de até 100% (Hartman et al, 1991;Kawuki et al, 2003;Yorinori, 2006).…”
Section: Introductionunclassified
“…P. pachyrhizi is an invasive fungal disease that can signiÞcantly reduce soybean yield (Kawuki et al 2003, Miles et al 2003. In the absence of P. pachyrhizi, inconsistent but positive yield responses are possible with the application of fungicide (Hanna et al 2008) through control of various (or multiple) fungal pathogens present in North America soybean (Dashiell and Akem 1991).…”
mentioning
confidence: 99%